PTH-045 Biliary aspirates in suspected pancreatic cancer. a useful adjunct to brushings at ERCP?. (June 2019) - Napier, Duncan; Arnold, Ben; Betteridge, Freddie; Masterman, Benjamin; Colleypriest, Ben
Abstract : Introduction: NICE guidelines advocate the use of biliary brushings to obtain a tissue diagnosis in patients suspected of having pancreatic cancer when endoscopic retrograde cholangiopancreatography (ERCP) is used to relieve biliary obstruction. This retrospective audit evaluated whether biliary aspiration in addition to biliary brushings increased diagnostic yields at ERCP at a district general hospital, reducing the need for tertiary referral for endoscopic ultrasound (EUS) and fine needle aspiration (FNA). Methods: Retrospective analysis of the local endoscopy database identified all patients undergoing ERCP with biliary brushings and aspirates between July 2012 and December 2018. Histological diagnoses from biliary aspirates/brushings were compared with subsequent FNA, surgical resection or hepatobiliary multi-disciplinary team diagnosis. Results: 124 patients underwent ERCP with biliary brushings during the study period. 28 of these patients had biliary aspirates in addition to biliary brushings. Sensitivity for biliary brushings in the whole population was 47.5% (95% CI 37.3–57.8) (table 1 ). Specificity was 96% (95% CI 79.7–99.9). In the cohort undergoing biliary brushings and aspirate, sensitivity for biliary brushings alone was 23.8% (CI 8.2–47.2), whilst combination of brushings and aspirates was 28.6% (95% CI 11.3–52.5). Conclusions: Biliary cytology has modest sensitivity with high specificity in the detection of malignancy at ERCP. Biliary aspirate cytology increases the positive yield by 5% compared to brushings alone and is a quick and easy technique at ERCP. Further data is required to evaluate whether biliary aspirates reliably increase the modest yield at ERCP, but this study shows a improvement from 23.8% to 28.6% in the subgroup who underwent both modalities to identify malignant cells at ERCP.